2006
DOI: 10.2174/138955706776073402
|View full text |Cite
|
Sign up to set email alerts
|

Rho-Kinase as a Drug Target for the Treatment of Airway Hyperresponsiveness in Asthma

Abstract: In asthma, inflammatory and structural cells contribute to increased bronchoconstriction acutely and more chronically to airway remodelling. Current asthma therapy doesn't inhibit these features satisfactorily. This review discusses Rho-kinase as a potential drug target, since increasing evidence suggests a central role for this pathway in acute and chronic airway hyperresponsiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 166 publications
(179 reference statements)
4
48
0
Order By: Relevance
“…The augmented BSM contraction induced by antigen exposure has reportedly been associated with an upregulation of RhoA (Chiba et al, 1999;2003;2005;2008;2009a;2009b;2009c), a small GTPase that is involved in the agonist-induced Ca 2+ sensitization of smooth muscle contraction (Somlyo and Somlyo 2003;Chiba and Misawa, 2004). The RhoA and its downstream Rho-kinases are now considered as a target of airway obstructive diseases such as asthma (Gosens et al, 2006;Kume, 2008;Schaafsma et al, 2008a;2008b). Although the promoter of the human RhoA gene is not fully understood until now to our knowledge, IL-4 is known to share many functional properties with IL-13 (Hershey, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The augmented BSM contraction induced by antigen exposure has reportedly been associated with an upregulation of RhoA (Chiba et al, 1999;2003;2005;2008;2009a;2009b;2009c), a small GTPase that is involved in the agonist-induced Ca 2+ sensitization of smooth muscle contraction (Somlyo and Somlyo 2003;Chiba and Misawa, 2004). The RhoA and its downstream Rho-kinases are now considered as a target of airway obstructive diseases such as asthma (Gosens et al, 2006;Kume, 2008;Schaafsma et al, 2008a;2008b). Although the promoter of the human RhoA gene is not fully understood until now to our knowledge, IL-4 is known to share many functional properties with IL-13 (Hershey, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that the agonist-induced, RhoA/Rho-kinase-mediated Ca 2+ sensitization of bronchial smooth muscle (BSM) contraction is augmented in rats (Chiba et al, 1999) and mice (Chiba et al, 2005) with allergic bronchial asthma. An importance of the RhoA/Rho-kinase system has also been demonstrated in human BSM (Yoshii et al, 1999), and the signaling of RhoA and its downstream Rho-kinases are now considered as a therapeutic target for the treatment of airway hyperresponsiveness in asthma (Gosens et al, 2006;Kume, 2008;Schaafsma et al, 2008a;2008b).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, however, a recent study raised a possibility that the activated STAT1 may have an ability to inhibit the expression of RhoA, 33) an important protein responsible for the AHR. 21,22,24,[34][35][36][37][38] Detailed studies are required to make clear the role of STAT1 in the development of AHR.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Hattori et al (2007) found that STAT1-deficient mice failed to develop the hyperresponsiveness of nasal airways that is usually induced by topical antigen challenge. In contrast, however, a recent study raised the possibility that activated STAT1 may have the ability to inhibit the expression of RhoA (Wang and Koromilas, 2009), an important protein responsible for BSM hyperresponsiveness (Chiba et al, 1999;2005;2008;2009a;2009b;Gosens et al, 2006;Kume, 2008;Schaafsma et al, 2008). Further studies are required to make clear the role of STAT1 in the development of BSM hyperresponsiveness.…”
Section: S T a T 1 I N B S M C S T H E M S E L V E S M I G H T B E I mentioning
confidence: 98%
“…Similarly, a cell-penetrating dominant-negative STAT6 peptide could inhibit AHR in a mouse model of allergic bronchial asthma (McCusker et al, 2007). In cultured bronchial smooth muscle cells, IL-13 can activate STAT6 directly, resulting in an upregulation of RhoA (Chiba et al, 2009a;2009b), a crucial protein responsible for AHR (Gosens et al, 2006;Kume, 2008;Schaafsma et al, 2008). On the other hand, recent studies also indicated the implication of other members of the STAT family of molecules, such as STAT1 (Quarcoo et al, 2004) and STAT3 (Simeone-Penney et al, 2007), in the development of AHR.…”
Section: Introductionmentioning
confidence: 99%